Odpowiedź i szczegółowe wyjaśnienie:
[tex]a)\ \\x=2-\sqrt{\sqrt{169}-\sqrt{16}\cdot\sqrt9}=2-\sqrt{13-4\cdot3}=2-\sqrt{13-12}=\\\\=2=\sqrt1=2-1=1\\DODATNIA\\\\\\b)\ \\x=\sqrt{65-8\sqrt{25}}-\sqrt{42-2\sqrt9}=\sqrt{65-8\cdot5}-\sqrt{42-2\cdot3}=\\\\=\sqrt{65-40}-\sqrt{42-6}=\sqrt{25}-\sqrt{36}=5-6=-1\\UJEMNA\\\\\\c)\ \\x=\sqrt{25\sqrt{25}-25}-\sqrt{9\sqrt9+9}=\sqrt{25\cdot5-25}-\sqrt{9\cdot3+9}=\\\\=\sqrt{125-25}-\sqrt{27+9}=\sqrt{100}-\sqrt{36}=10-6=4\\DODATNIA\\\\\\[/tex]
[tex]d)\ \\x=\sqrt{\sqrt{121}-\sqrt4}-\sqrt{\sqrt{144}+\sqrt{16}}=\sqrt{11-2}-\sqrt{12+4}=\\\\=\sqrt{9}-\sqrt{16}=3-4=-1\\UJEMNA[/tex]